Enabling dual-core mode in BlueGene/L: challenges and solutions - Almasi, G.; Bachega, L. R.; Chatterjee, Siddhartha; Gupta, Manish; Lieber, D.; Martorell, X.; Moreira, J. E. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2003)
BlueGene/L is a massively parallel computer system with 65536 dual-processor compute nodes. The peak performance of BlueGene/L is in excess of 360 TFLOP/s if both processor cores in a node are used for computation. The main challenge of deploying this dual-core mode of operation is that the L1 caches in each core are not hardware coherent. This forces a software-based approach to cache coherence and guides our design of a programming model for dual-core mode. We describe the design, implementation, and performance evaluation of system software for enabling the use of dual-core mode on BlueGene/L. Our preliminary performance results show that our approach to dual-core mode is effective for key numerical kernels.